2020
DOI: 10.3390/brainsci10050290
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in Early Somatosensory Evoked Potentials between the Dominant and Non-Dominant Hand, Following a Novel Motor Tracing Task

Abstract: During training in a novel dynamic environment, the non-dominant upper limb favors feedback control, whereas the dominant limb favors feedforward mechanisms. Early somatosensory evoked potentials (SEPs) offer a means to explore differences in cortical regions involved in sensorimotor integration (SMI). This study sought to compare differences in SMI between the right (Dom) and left (Non-Dom) hand in healthy right-handed participants. SEPs were recorded in response to median nerve stimulation, at baseline and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…The current study noted an increase in the N30 in both groups after completing the novel force-matching task (FMT). Previous work has found that motor acquisition paradigms result in an increase in the N30 SEP peak amplitude (Andrew et al, 2015a,b;Zabihhosseinian et al, 2020). Recent work utilizing a novel force-matching task (FMT) found an increase in the N30 SEP peak after the learning paradigm was complete (Ambalavanar et al, 2022).…”
Section: N30mentioning
confidence: 99%
“…The current study noted an increase in the N30 in both groups after completing the novel force-matching task (FMT). Previous work has found that motor acquisition paradigms result in an increase in the N30 SEP peak amplitude (Andrew et al, 2015a,b;Zabihhosseinian et al, 2020). Recent work utilizing a novel force-matching task (FMT) found an increase in the N30 SEP peak after the learning paradigm was complete (Ambalavanar et al, 2022).…”
Section: N30mentioning
confidence: 99%